Revisiting Behaviourism Theory of Learning: an outline with Islamic Education - Khairan Muhammad Arif (Universitas Darussalam Gontor, 2022)
Research on the correction of the theory of learning behaviorism perspective of Islamic education aims to reveal and explain the weaknesses of the theory of learning behaviorism introduced and practiced by the figures of the psychological school of behaviorism such as; Edwart L. Thorndike (1874-1949), Ivan Pavlov (1849-1936) and B. F Skinner (1904-1990), especially related to the concept of learning, the nature of learners and the motivation of learning that many educational practices conventional western, then provides a more precise and comprehensive concept related to learning, the nature of human or learner potential and learning motivation in the Qur'an and As-Sunnah. This research method uses a qualitative method with an analytical description approach that aims to explain and describe the problems studied authentically, literatively and thematically, as well as scientifically analyze the research object that gives birth to conclusions. The source of this research is the library (Library Research), by tracing and examining a large part of the main references to the theory of behaviorism such as the work of B.F. Skinner, Science and Human Behavior, works Robert M. Gagne, The Condition of Learning and Theori of Instruction